Linearly Polarization-Sensitive Perovskite Photodetectors - Sun, Jie; Ding, Liming (Nano-Micro Letters, 2023)
Highlights: 1 Polarization is an exceptional physical property of light that carries and differentiates a significant amount of optical information. Perovskite materials are utilized in polarization-sensitive photodetectors owing to their crystal structure anisotropy and controllable orientation growth, in addition to their excellent photovoltaic performance. 2 This paper presents an overview of the structural characteristics and photovoltaic performance of different optical structures and low-dimensional perovskite polarization photodetectors. This summary will contribute to the future development of perovskite-based photodetectors that are sensitive to polarization.